In-the-bag toric intraocular lens implantation in the case of an anterior capsule tear: a case series - Dervenis,Panagiotis (2019)
ABSTRACT Purpose: To analyze the outcomes of in-the-bag toric intraocular lens implantation for anterior capsular tears during phacoemulsification. Methods: The cohort of this retrospective, consecutive, interventional case series included eight patients. One patient was excluded as the tear was used to enlarge the rhexis. The mean preoperative astigmatism was -1.67D (± 0.98) and the mean preoperative unaided logMAR visual acuity was 0.62 (± 0.76). The mean angle between the anterior capsule tear and the closest intraocular lens haptic was 51.25° (range, 30°-90°). Results: The final unaided logMAR visual acuity was 0.16 (± 0.21) and the final cylinder was -1.1 D (± 0.59). The mean follow-up duration was about 2 ± 1.2 months. In this case series, no lens had to be explanted or rotated postoperatively. Placement of a toric intraocular lens in the presence anterior capsule tear was safe in all patients. An angle of at least 30° remained between the tear and the intraocular lens haptic. Conclusion: Placement of toric intraocular lens in the presence of an anterior capsule tear may be safe, at least in cases with a 30° angle between the anterior capsule tear and the intraocular lens haptic.